Synthesis, Characterisation and Cardiac Activity of Some Novel 2,3-Substituted-4-phenyl-1,3-oxazolidine Derivatives - Gudaprthi, Vijayalakshmi; Bharathi , K.; Omprakash, G. (Asian Journal of Chemistry, 2010)
A series of 2,3-substituted-4-phenyl-1,3-oxazolidine derivatives were synthesized from DL- (±)-phenyl glycine. DL-(±)-Phenyl glycine was reduced to the corresponding alcohol, which was then condensed with different aldehydes to form Schiff bases, which are then reduced and further condensed with different substituted aldehydes to give the oxazolidine derivatives. The synthesized compounds are characterized by 1H NMR, IR and mass spectral analysis. All the compounds were investigated for cardiac activity while all the compounds show significant activity.